2016
DOI: 10.1093/glycob/cww111
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the human polypeptide GalNAc-T1 and T13 paralogs

Abstract: Polypeptide GalNAc-transferases (GalNAc-Ts) constitute a family of 20 human glycosyltransferases (comprising 9 subfamilies), which initiate mucin-type O-glycosylation. The O-glycoproteome is thought to be differentially regulated via the different substrate specificities and expression patterns of each GalNAc-T isoforms. Here, we present a comprehensive in vitro analysis of the peptide substrate specificity of GalNAc-T13, showing that it essentially overlaps with the ubiquitous expressed GalNAc-T1 isoform foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…We only found a few sites unique for GalNAc-T1 in contrast to T2 and T3, however, this may be related to low levels of expression of the close isoform GALNT13 (Fig. 1A), which has very similar activity (29). In our previous study in HepG2 cells we identified a considerably larger number of nonredundant GalNAc-T1 isoform-specific candidates (5), and expression of GALNT13 is not detectable by RNAseq.…”
Section: Molecular and Cellular Proteomics 187 1399mentioning
confidence: 65%
“…We only found a few sites unique for GalNAc-T1 in contrast to T2 and T3, however, this may be related to low levels of expression of the close isoform GALNT13 (Fig. 1A), which has very similar activity (29). In our previous study in HepG2 cells we identified a considerably larger number of nonredundant GalNAc-T1 isoform-specific candidates (5), and expression of GALNT13 is not detectable by RNAseq.…”
Section: Molecular and Cellular Proteomics 187 1399mentioning
confidence: 65%
“…In fact, we and others have detected putative splice variants for other PGANT and GALNT family members (39,40). For example, splicing of the human GALNT13 alters both the length and charged residues within the g repeat of the lectin domain (39,40). This splicing event results in changes in the affinities for certain glycopeptide substrates but does not appear to alter directionality of GalNAc addition to glycopeptides (39,40).…”
Section: Discussionmentioning
confidence: 78%
“…Because lectin and catalytic subdomains lie in exonic regions of other members of this family (1), it suggests that splicing events that modify these domains may be used more widely by other PGANTs/ GALNTs. In fact, we and others have detected putative splice variants for other PGANT and GALNT family members (39,40). For example, splicing of the human GALNT13 alters both the length and charged residues within the g repeat of the lectin domain (39,40).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, a recent study by May et al ( 2020 ) has shown that alternative splicing of PGANTs, the Drosophila analogues of mammalian ppGalNTs ( Table 1 ), which catalyse the addition of the glycan to serine or threonine, can alter the substrate and peptide preference of the enzyme. Even though this study investigates Drosophila PGANTs, a previous study has demonstrated the presence of splice variants in humans (Festari et al, 2017 ). Whether the splice variants of human ppGalNTs also affect the recognition of substrate in the same manner as the Drosophila splice variants and whether this impacts leukocyte recruitment remains unknown.…”
Section: Glycans and Glycan Binding Proteins In Leukocyte Capture Andmentioning
confidence: 99%